Multifunctional Bioorganic Fertilizer - C. K. H. Phua (2013)
Malaysian Nuclear Agency (Nuclear Malaysia) has developed a series of multifunctional bioorganic fertilizers, which include an organic fertilizer called ORGANIC NF and two multifunctional bioorganic fertilizers namely, MULTIFUNCTIONAL BIOFERT PG & PA, in reducing dependency on chemical fertilizer for crop production. These products use 100% natural products, with no added chemicals. They are, thus, a 'Green Product' - environmental friendly, optimizing the bioresources, pathogen-free, and are suitable for many crops, including vegetables, fruits trees and ornamentals, under different framing systems - plantation, orchards, greenhouses, soilless-systems and nurseries.